Shiite Azerbaijan Academy’s Approach to Alevism - Topuz, Birol (Journal of Alevism-Bektashism Studies, 2024)
Relations between Azerbaijan and Turkey are of vital importance for the Caucasus region. It has been seen once again how strong this is, especially during the recent Karabakh-War. Although these two countries have built their relations on the axis of the concept of “nationalism” until now, it is also known that these two countries adhere to different branches of Islam such as Sunni-Shia. It cannot be said that this difference of belief has negatively affected the relations between the two countries until today. Especially in the recent conflict between Israel and Palestine, it is seen as an unusual situation that the two countries support different sides. It is noteworthy that, for the first time in recent history, the Azerbaijani state-owned enterprise, SOCAR, experienced an attack in Turkey. This incident occurred in the context of the ongoing conflict between Israel and Palestine. The significance lies in the fact that this represents the first recorded instance of an assault on an Azerbaijani institution within Anatolia. An intriguing aspect to consider is how this unprecedented event may impact bilateral relations between the two countries moving forward, especially concerning regional security dynamics.Another important thing that will trigger this extraordinary phenomenon is the perception of Shiism in the context of Alevi-Sunni relations. Although many studies on Shiites in Turkey, there is not enough information in the literature about Shiites, especially Alevis living in Turkey. Therefore, this gap in the literature highlights this issue as an alternative worthy of study in this field.As it is known, Alevism in Turkey is perceived as Shiism by some Sunnis. However, Shia and Alevism seem to have almost nothing in common except the love for Caliph Ali and the Twelve Imams. Neither the institutions and religious practices nor the sources of Alevism resemble Shism. What is the level of knowledge of Azerbaijani Shias about Alevism and Alevis in Turkey? This study is designed to investigate the answer to this question.
Keywords: Alevism; Shia; Sunni; Turkey; Azerbaijan